2018
DOI: 10.1016/j.actbio.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Permeability mapping of gelatin methacryloyl hydrogels

Abstract: GelMA hydrogels have attracted increasing attention in recent years as matrices for cell cultures and biomolecule delivery. This inexpensive polymer is derived from gelatin functionalized with methacryloyl groups that can be crosslinked by photochemical reactions. Here we report the development of an efficient, customized testing method to systematically estimate the hydraulic permeability of GelMA hydrogels. Hydraulic permeability indicates the resistance of GelMA hydrogels to the movement of saturated fluid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 55 publications
1
67
0
1
Order By: Relevance
“…However, it should be noted that these permeability values represent those in the bioprinted hollow channels only and not when encapsulated in the hydrogel matrices. The permeability of the latter can be directly calculated using our recently developed model [73] .…”
Section: Permeability Evaluations Of the Bioprinted Hollow Tubesmentioning
confidence: 99%
“…However, it should be noted that these permeability values represent those in the bioprinted hollow channels only and not when encapsulated in the hydrogel matrices. The permeability of the latter can be directly calculated using our recently developed model [73] .…”
Section: Permeability Evaluations Of the Bioprinted Hollow Tubesmentioning
confidence: 99%
“…These nanopores are indicative of interchain distances that might be formed by the crosslinked polymer chains within the GelMA hydrogel. [17]…”
Section: Synthesis Of Hierarchically Macro-micro-nanoporous Cell-ladementioning
confidence: 99%
“…When fully crosslinked, a hydrogel with a high DoF will display high stiffness and smaller mesh size. Furthermore, a higher stiffness means that the enzymatic degradation rate by metalloproteinase decreases, which is critical for in vivo applications [46]. An increase in GelMA concentration decreases the mesh size and therefore increases the hydrogel stiffness [47].…”
Section: Materials Characterizationmentioning
confidence: 99%
“…An increase in mesh size increases the diffusion rate, whereas reduced mesh size can slow down the diffusion or entrap the drug in the matrix [33]. Miri et al studied the impact of the DoF and curing conditions on hydrogel stiffness and reported a slower release rate of bovine serum albumin when the GelMA concentration was increased [46]. More precisely, it is the difference between mesh size and drug size that controls drug diffusion rates.…”
Section: Introductionmentioning
confidence: 99%